2012
DOI: 10.1111/j.1439-037x.2012.00504.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Zinc and Cadmium Levels on Root Antioxidative Responses in Three Different Zinc‐Efficient Wheat Genotypes

Abstract: This work was undertaken to investigate the effect of zinc (Zn) nutrition on root antioxidative responses to cadmium (Cd) toxicity of three wheat genotypes differing in Zn efficiency. A hydroponic experiment was carried out in which two bread wheat genotypes (Triticum aestivum L. cvs. ‘Rushan’ and ‘Cross’) and one durum wheat genotype (Triticum durum L. cv. Durum) were exposed to three Zn2+ (10−11.11, 10−9.11 and 10−8.81 μm) and two Cd2+ (10−11.21 and 10−10.2 μm) activity levels. ‘Durum’ showed the highest roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…The lower level of Zn increased the activities of CAT and APX in Cd-stressed wheat roots while higher Zn decreased enzyme activities, but this increase was dependent on the crop genotype and Zn levels in the media (Sanaeiostovar et al, 2012). Decrease in Cd concentrations in durum wheat grains might be due to competitive inhibition of Cd loading into phloem sap by Zn as suggested by Cakmak et al, (2000a).…”
Section: Mineral Fertilizationmentioning
confidence: 83%
“…The lower level of Zn increased the activities of CAT and APX in Cd-stressed wheat roots while higher Zn decreased enzyme activities, but this increase was dependent on the crop genotype and Zn levels in the media (Sanaeiostovar et al, 2012). Decrease in Cd concentrations in durum wheat grains might be due to competitive inhibition of Cd loading into phloem sap by Zn as suggested by Cakmak et al, (2000a).…”
Section: Mineral Fertilizationmentioning
confidence: 83%
“…Blommaert [27] reported that the liming of the soil may mitigate the Cd uptake only if the subsoil layers are not rich in Cd. Appropriate mitigation strategies of Cd uptake on cacao trees are therefore needed, and additional studies are encouraged in the field rather than in controlled conditions [28]. In cacao plantations in South America, management factors such as the use of fertilizers, pesticides, irrigation, organic farming [29] and forestry, as well as plant biodiversity, have been related to the total Cd contents in cacao plantation soils [19] and cacao beans [22].…”
Section: Introductionmentioning
confidence: 99%
“…, Sanaeiostovar et al. ). The difference in activities of these antioxidant enzymes between root‐restricted plants and controls indicates that the deep roots have a high potential to scavenge ROS in response to environmental stresses.…”
Section: Discussionmentioning
confidence: 99%
“…, Sanaeiostovar et al. ). In wheat, topdressing N at the shooting stage could enhance root activity, increase SOD activity and decrease malondialdehyde (MDA) content, and root activity is positively correlated with leaf photosynthesis rates (r = 0.8006) (Wei et al.…”
Section: Introductionmentioning
confidence: 99%